2010
DOI: 10.1073/pnas.1007074107
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Trypanosoma brucei gambiense (group 1) resistance to human trypanosome lytic factor

Abstract: Human innate immunity against most African trypanosomes, including Trypanosoma brucei brucei, is mediated by a minor subclass of toxic serum HDL, called trypanosome lytic factor-1 (TLF-1). This HDL contains two primate specific proteins, apolipoprotein L-1 and haptoglobin (Hp)-related protein, as well as apolipoprotein A-1. These assembled proteins provide a powerful defense against trypanosome infection. Trypanosoma brucei rhodesiense causes human African sleeping sickness because it has evolved an inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
122
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(128 citation statements)
references
References 29 publications
(32 reference statements)
6
122
0
Order By: Relevance
“…Previous studies demonstrated that SRA binds TLF-1 via apoL-1 (39) and that these proteins colocalize in intracellular vesicles (25). Since SRA traffics to the flagellar pocket, which is also the site of receptor- (20). In these cells, SRA-Ty localized to the flagellar pocket, based on localization studies at 3°C with anti-Ty ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that SRA binds TLF-1 via apoL-1 (39) and that these proteins colocalize in intracellular vesicles (25). Since SRA traffics to the flagellar pocket, which is also the site of receptor- (20). In these cells, SRA-Ty localized to the flagellar pocket, based on localization studies at 3°C with anti-Ty ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…brucei HpHbR (Leu210) leads to reduced affinity for human Hp-Hb and Hpr-Hb 7,27,28 . In combination with lowlevel expression of HpHbR 26 and the protective effect of TgsGP 22 , this evolutionary amino-acid substitution contributes to T.b. gambiense resistance against the human TLF particles.…”
Section: Structure Determinationmentioning
confidence: 99%
“…T.b. gambiense also exhibits low-level HpHbR expression 26 and harbours a L210S substitution in HpHbR, leading to reduced TLF1 uptake 7,27,28 . These defence mechanisms are not present in the widespread Trypanosoma brucei brucei (T.b.…”
mentioning
confidence: 99%
“…Trypanosoma brucei brucei is sensitive to trypanolytic factors present in human serum and therefore fails to establish infection in humans. T. brucei brucei can, however, cause disease in some livestock 2 . The disease runs a complex course leading to death if left untreated in both animals and humans.…”
Section: Introductionmentioning
confidence: 99%